The association of meniscal damage with joint effusion in persons without radiographic osteoarthritis: the Framingham and MOST osteoarthritis studies. - Roemer, F; Guermazi, A; Hunter, D; Niu, J; Zhang, Y; Englund, M; Javaid, M; Lynch, J; Mohr, A; Torner, J; Lewis, C; Nevitt, M; et al. (2009)
OBJECTIVE: To assess the cross-sectional association between meniscal status and joint effusion on magnetic resonance imaging (MRI) in knees without radiographic osteoarthritis (OA). DESIGN: Knees without OA (Kellgren/Lawrence grade 0) from the Framingham and MOST studies were examined by MRI. Meniscal status was assessed with a score of 0-4 in the anterior horn/body/posterior horn of the medial/lateral meniscus and effusion was assessed using a score of 0-3. The odds ratios (ORs) of joint effusion in those with meniscal damage were estimated using a logistic regression model. A subanalysis was performed for knees without MRI-detected cartilage damage. RESULTS: Of 1368 knees, 296 (21.6%) showed meniscal pathology in at least one subregion. Effusion was present in 133 (44.9%) of knees with meniscal damage vs 328 (30.6%) in those without meniscal damage. The adjusted OR of effusion in a knee with meniscal damage was 1.8, 95% confidence intervals (CI) [1.4, 2.4]. The OR of effusion for the group with meniscal pathology in two compartments was 5.4, 95% CI [2.1, 14.3]. For knees without any cartilage lesions but with meniscal damage in any compartment the OR was 2.3, 95% CI [1.1, 4.5]. CONCLUSIONS: Knees without OA but with meniscal pathology exhibit joint effusion to a significantly higher degree than knees without meniscal damage. The association persists for knees without cartilage damage. The prevalence of effusion is further increased when present in two compartments. Concomitant occurrence of synovial activation and meniscal damage contributes to understanding the pathophysiology of early degenerative joint disease.